Mejorar la salud, una cuestión ciudadana - Gil-Lacruz, Marta; Barrantes Ollauri, Juan Manuel; Matute Bravo, Silvia; Cecilia Marquina, Ana Santa; González Arratia, Norma Ivonee (CIENCIA ergo-sum; Vol. 6 Núm. 3 (1999): CIENCIA ergo-sum (noviembre 1999-febrero 2000), 2017)
-